Assessing microbial diversity in soil and roots of common crops in Sapa district, Lao Cai province, Vietnam - Thi Nhat, Phuong Bui; Yen, Chi Nguyen; Nam, Le Quang; Dung, Le Viet; Herrmann, Laetitia; Lesueur, Didier (2024)
Agricultural productivity is intricately linked to the health and biodiversity of soil, making the study of these components paramount in understanding and enhancing crop production. As the foundation of terrestrial ecosystems, soil health and biodiversity play pivotal roles in nutrient cycling, disease suppression, and overall ecosystem resilience (Berendsen et al., 2012). Microbial diversity has been recently attracted increased attention in the field of soil science, microbiology and biodiversity. Studying on soil microbial diversity are of great significance for exploring natural biological mechanisms, coping with global climate change, controlling environmental pollution, maintaining ecological functions and promoting sustainable use of soil. However, in recent years, multiple studies have demonstrated that human activities, including agricultural intensification and changes in land use, along with climate change, are diminishing the soil's ability to carry out essential processes and functions (M et al., 2016). This has raised growing concerns that diminished soil biodiversity could adversely affect numerous ecosystem functions and services (C et al., 2014; Sf et al., 2016). Natural factors, including agricultural vegetation type (Han et al., 2007), soil type (Marschner et al., 2001), temperature and moisture (Rinnan et al., 2009); and human factors, including pesticides, fertilization, and soil tillage methods (Zhang et al., 2019) can significantly affect the microbiome in their roots and surrounding area. Vietnam, with its robust agricultural potential, stands as a noteworthy context for this investigation. Particularly, Northern Vietnam has favorable weather conditions and geographical features that create an ideal environment for farming (Vien, 2003). The region's agricultural significance underscores the need for a well understanding of the microbial communities that contribute to soil health and plant growth. The studied site was Sapa District, Lao Cai Province, Vietnam. The research site selected for this study was the Sapa District in Lao Cai Province, Vietnam, situated at an elevation of 1,600 meters above sea level. Sapa District benefits from a humid, temperate subtropical climate with cool air throughout the year, with an average annual air temperature of 15oC. For the study, Rice, Maize, and Home garden vegetables in Thanh Binh and Muong Hoa villages were chosen due to variations in their utilization of fertilizers (NPK or Urea) and/or pesticides and herbicides. Muong Hoa commune, known for its tourism, primarily engages in agricultural activities for tourism purposes, whereas Thanh Binh more focuses on production activities. The analysis contained of bacterial and fungal communities in soil and arbuscular mycorrhizal fungi (AMF) communities in roots. This research aims to contribute to the database of soil microbial diversity, including bacteria, fungi, and arbuscular mycorrhizal fungi (AMF) associated with various crop types in Vietnam. Furthermore, it seeks to investigate whether differences in fertilizer application between the two communes result in variations in microbial diversity. Additionally, by analyzing the relationship between soil characteristics such as pH, carbon (C), phosphorus (P), organic matter (OM), and microbial communities, this study aims to provide deeper insights into the soil health.